Stabilizing organic matter and reducing methane emissions during manure composting with biochar to strengthen the role of compost in soil health - Keiji Jindo; Tomonori Sonoki; Miguel A. Sánchez-Monedero (Soil & Environmental Health, 2025)
Biochar is a promising additive for enhancing composting efficiency and long-term compost quality. This study investigated its effects on greenhouse gas emissions and organic matter stabilization during the composting of poultry (PM) and cattle manure (CM). Biochar addition significantly reduced methane emissions during the thermophilic phase—by 4.6-fold in PM+B and 3.7-fold in CM+B compared to PM and CM without biochar amendment, respectively—indicating improved aeration and microbial activity, as supported by higher CO2 emissions. A novel aspect of this study is the focus on lignin, a recalcitrant carbon fraction. Biochar-amended composts showed 1.5-fold greater lignin degradation (29.0 ​% in PM ​+ ​B and 10.8 ​% in CM ​+ ​B) than controls, along with enhanced lignin stability, as evidenced by Nuclear Magnetic Resonance spectroscopy and thermal analysis. We assessed labile carbon fractions (e.g., water-soluble carbon and carbohydrates), ATP, and enzymes involved in carbon and nutrient cycling. PM and CM retained more labile carbon through the final stage, showing higher ATP, dehydrogenase, and β-glucosidase than their biochar-treated counterparts. Redundancy analysis indicated that microbial communities and structural traits influenced gas emissions during the thermophilic stage and compost stabilization at the final stage. CH4 emissions were associated with mcrA, fungi, and total nitrogen, while CO2 correlated with bulk density and Gram-negative bacteria. In the final stage, maturity indices were linked with microbial and physicochemical variables, underscoring their combined role in compost stabilization. Biochar amendment enhanced compost quality by reducing CH4 emission and promoting selective carbon transformation, particularly lignin. These findings support biochar-amended composting as a strategy for producing composts with improved agronomic and environmental value.